Pemberian Simulasi Wawancara Kerja pada Generasi Gen Z di Kota Bandung - Rifqi Farisan Akbar; Yoyo Sudaryo; Pratidina Ekanesia; Gunawan Dayona Ismail; Andre Suryaningprang; Riyandi Nur Sumawidjaja; Ridlwan Muttaqin (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Generation Z faces increasingly intense competition in the labor market; however, many individuals continue to encounter difficulties during job interviews due to limited experience, low self-confidence, and insufficient professional communication skills. This study aims to analyze the implementation of job interview simulations and examine their impact on the job readiness of Generation Z in Bandung City. The study employed a descriptive-evaluative method involving 45 Generation Z participants. Data were collected through observation, performance assessments, documentation, and participant feedback. The findings indicate that job interview simulations effectively enhanced participants’ readiness, as evidenced by 85% of participants reporting that they felt highly prepared and confident, while the remaining 15% reported feeling prepared and confident after completing the program. Interviewers’ evaluations revealed that 70% of participants demonstrated a very good improvement in their ability to respond to interview questions, 18% showed good improvement, and 12% exhibited fairly good improvement. Participant satisfaction with the program was also notably high, with 77% reporting being very satisfied, 15% satisfied, and 8% fairly satisfied with the implementation of the activity. The results confirm that job interview simulations are effective in improving participants’ self-confidence, communication competence, and overall job readiness. The novelty of this study lies in the application of interview simulations based on authentic recruitment scenarios, evaluated through the dimensions of job readiness, communication competence, and participant satisfaction, thereby offering a practical career development model for Generation Z.